2015
DOI: 10.1007/s10875-015-0157-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Two Japanese Adenosine Deaminase-Deficiency Patients Treated by Stem Cell Gene Therapy with No Cytoreductive Conditioning

Abstract: ObjectiveWe here describe treatment outcomes in two adenosine deaminase (ADA)-deficiency patients (pt) who received stem cell gene therapy (SCGT) with no cytoreductive conditioning. As this protocol has features distinct from those of other clinical trials, its results provide insights into SCGT for ADA deficiency. Patients and MethodsPt 1 was treated at age 4.7 years, whereas pt 2, who had previously received T-cell gene therapy, was treated at age 13 years. Bone marrow CD34 + cells were harvested after enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…A favorable influence of TGF-β on HSC retention is consistent with our previous reports [13,15]. Positive effects of IL-6 on HSC culture are well known, as exemplified by its use in a cytokine cocktail in clinical trials [16][17] where expansion of human CD34+ cells was the goal. That IL-1β promoted retention of primitive cells is an unexpected observation in light of its reportedly negative effects on HSCs' reconstituting ability [18].…”
Section: Discussionsupporting
confidence: 89%
“…A favorable influence of TGF-β on HSC retention is consistent with our previous reports [13,15]. Positive effects of IL-6 on HSC culture are well known, as exemplified by its use in a cytokine cocktail in clinical trials [16][17] where expansion of human CD34+ cells was the goal. That IL-1β promoted retention of primitive cells is an unexpected observation in light of its reportedly negative effects on HSCs' reconstituting ability [18].…”
Section: Discussionsupporting
confidence: 89%
“…In 2015, we reported two patients with ADA-SCID who were treated with retrovirus-mediated gene therapy 18 . Although PEG-ADA replacement was withdrawn in our trial, the patients never received preconditioning chemotherapy before the transplantation of gene-modified HSCs; therefore, partial and temporal reconstitution of the immune system was observed in both patients.…”
Section: Introductionmentioning
confidence: 91%
“…Vector integration-site analyses confirmed that hematopoiesis was reconstituted by a limited number of clones, some of which had myelo-lymphoid potential. These results emphasize that cytoreductive conditioning is important for achieving optimal benefits from SCGT [30] (Table 3).…”
Section: Scid)mentioning
confidence: 65%